Vpliv količine plinov v vodi in hitrosti toka na agresivnost kavitacijske erozije - Dular, Matevž (Strojniški vestnik, 2005)
A study of the influence of the gas content of water and the flow velocity on cavitation erosion aggressiveness was performed. A cavitation tunnel with a single hydrofoil was used for the experiments. While the cavitation number andthe mean flow velocity remained constant throughout the tests, the gas content of the water was changed in steps from low (approximately 1%) to high (4 %). The gas content of the water was adjusted with a bubble generator. In addition tests at a constant cavitation number and water gas content but different mean flow velocities (10, 13 and 16 mžs) were made. A thin copper foil, applied to the surface of the hydrofoil, was used as an erosion sensor. Images of the damaged, copper-coated hydrofoil surface were taken at an appropriate magnification. A pit-count method, based on computer-aided image processing, was used for direct measurements of the cavitation erosion by evaluating the damage on the surface of the hydrofoil. Clear evidence for the influence of the gas content and the velocity on the erosion intensity was found. The cavitation erosive aggressiveness exponentially drops when the content of the water is increased. A power law was confirmed for the velocity's influence on the cavitation erosive aggressiveness. The presented results promise the possibility of deriving a cavitation erosion model and the possibility of cavitation erosion prediction using only numerical tools in the future.
Keywords: kavitacija; erozija; plini v vodi; količine plinov; hitrosti tokov; tokovne razmere; gibanje tekočin